Consent form, the highest ethical standard in creating DNA databases for criminal investigation - Jankova, Renata; Donevska-Stefanov, Pavlinka; Bitoljanu, Natasha; Pavlovski, Goran; Janevski, Robert; Stankov, Aleksandar (Elsevier BV, 2022)
Preparation of DNA databases for the purpose of criminal investigation opens discussions about ethical-legal issues concerning violation of human rights. The practice shows that one of the human rights that can be misused while creating such a database is the right to freedom, the freedom to make a decision. When preparing DNA databases, the right to freedom refers to free decision of the person to be sampled for carrying out the test. The right to freedom and respect to self-determination of the person implies the necessity of prior consent of the subject when preparing a database on general population level. This is not a case when databases are created from persons under investigation for committing a crime, who are compulsory subjected for obtaining samples for DNA analysis. Legal regulations approve the duty of the police and its authorization in collecting samples for personal or criminalistic identification, analyzing, keeping and eliminating collected personal information when criminal prosecution is concerned. In these cases, consent form from the subject is not necessary. However, we should be aware that the process of taking and collecting of personal information by the national institutions can have direct impact of privacy of the subject, no matter if this information is going to be used or not. In purpose of fair balance between public and private interest, consent form can be redefined and the person from whom the biological material is provided will be unequivocally made aware of the purposes for which his genetic data will be used, how long his DNA will undergo further automated processing, and about the procedure and under what conditions his DNA profile can be removed from the national DNA databases.
Keywords: Ethical consideration; DNA databases; Consent form